Happy City strategy, satisfying individuals' needs by sustainable urban design (Zurich and Dubai as models) - Makki Tiba M; Khalid Zainab (E3S Web of Conferences)
Well-being and prosperous living are among the most significant goals of sustainable development, and development strategies should be directed toward satisfying individuals’ needs and living in happy cities. The research explores the potential for establishing a comprehensive strategy by examining different approaches to urban planning and their impact on individuals’ happiness. The research problem is the absence of a clear, standardized vision for developing cities that satisfy individuals’ needs and promote happiness. The hypothesis suggests exploring urban development strategies for the happiest cities in the world to satisfy individuals’ needs and promote happiness. Relying on the concept of the happy city, sustainability, and individuals’ needs and examining the success of Zurich and Dubai cities, the research aims to explore urban elements within cities that satisfy individuals’ needs and promote happiness and seeks to develop a comprehensive framework for a happy city strategy that can be applied to promote happiness for Iraqi cities using measurable indicators to assess their achievement levels and improve urban well-being. Using a descriptive-analytical and comparative approach, the findings show that sustainable urban design can positively impact individuals’ happiness by satisfying their needs and presents a comprehensive, actionable strategy to develop cities towards happiness relying on built and natural environmental elements that promote sustainable developments and happiness, which are crucial for the practical application of these findings.